The Integration of a Fragmented Self in the Works of Angelina Muñiz-Huberman - Malva E. Filer (Studies in 20th & 21st Century Literature, 2003)
Literary creation is always a transposition of individual and collective experiences…
Keywords: fragmentation; self; identity; Angelina Muñiz-Huberman; literary creation; individual; collective; experience; Mexican literature